Protective Efficacy of Cholesterol-Loaded Cyclodextrin (CLC) Against Sperm Morphological Abnormalities in Marwari Stallions - Kumar, Pramod; Mehta, J S; Ravi, S K; Talluri, T R; Kumawat, B L; Kumar, Tapendra; Kumar, Shivendra; Jhamb, D; Dedar, Ramesh Kumar (Animal Reproduction Update, 2023)
The present study aimed to examine the protective potential of cholesterol loaded  cyclodextrin (CLC) at varying concentrations against sperm morphological  abnormalities of cooled and frozen thawed semen of Marwari stallions. A total  of forty eight ejaculates (six stallions and eight ejaculates per stallion) were  promptly processed following semen collection and subjected to gross assessment  of semen quality attributes. The assessment of sperm morphologies in fresh  equine semen was conducted using Eosin and Nigrosine staining technique. The  semen samples from individual Marwari stallions were evenly divided into five  fractions and incubated in a water bath at 37°C for 15 min after dilution with  primary extender to obtain the spermatozoa concentration at 120 × 106 sperm/ml.  During incubation, the fractions of every semen sample were exposed to different  concentrations of CLC as 0, 1.0, 1.5, 2.0 and 3.0 mg/ml of extender (C, T1, T2,T3,  and T4, respectively). All the 5 aliquots were cooled and subsequently subjected  to cryopreservation. Each cooled and frozen- thawed (at 37°C for 30 sec) semen  samples were analyzed to assess the morphologies of the spermatozoa. Based on  the findings, it was concluded that none of the CLC treatment could render any  significant protection against the sperm morphological abnormalities at either  pre-freeze and/or post-thaw stage of semen samples from Marwari stallions.
Keywords: Cholesterol loaded cyclodextrins; cryopreservation; Marwari stallion; sperm abnormalities